Gambaran Anatomi dan Histologi Usus Besar Ayam Hutan Hujau (Gallus varius) Asal Pulau Alor - Yuni Sarah Sidabutar; Inggrid T. Maha; Filphin A. Amalo; Heny Nitbani (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2022)
Green jungle fowl (Gallus varius) is one of Indonesia's endemic poultry species, which is often used by the community to produce high-value ornamental birds. This study aims to determine the anatomical morphology and histology of the large intestine of green jungle fowl. Colon samples were taken from 3 green jungle fowl collected in Alor Regency. The obtained samples were observed macroscopically and then fixed using 10% formalin, then processed into histological preparations and stained with hematoxylin-eosin (HE). The results showed that the large intestine of the green jungle fowl consisted of a pair of cecum and a rectum. The location of the cecum and rectum of green jungle fowl is the same as that of poultry in general, which is located in the peritoneal cavity, adjacent to other intestinal segments. Each cecum consists of 3 parts, namely proximal, corpus, and apex. The cecum is pale red in color with a soft consistency. The average cecum length of the green jungle fowl is 10.9 cm. The rectum is the last segment of the intestine in the form of a straight channel that connects the ileum and cloaca. The rectum is pale red in color, soft in consistency and has thicker walls than the rest of the intestine. The average length of the rectum of the green jungle fowl is 3.9 cm. Histologically the cecum and rectum walls of green jungle fowl are composed of tunica mucosa, tunica submucosa, tunica muscularis and tunica serosa. The wall layer of the large intestine of green jungle fowl is generally the same as other birds, but differs in the muscularis tunica, namely circular smooth muscle fibers located on the outside and longitudinal smooth muscle on the inside.